Design and Evaluation of a Thermal Tactile Display for Colour Rendering. (16th November 2015) - Jia, Zhen; Li, Jianqing; Chen, Congyan
This paper proposes a novel method of manipulating both thermal change rate and thermal intensity to convey colour information by using a thermal tactile display. The colour-space transformation from red, green, blue to hue, saturation, intensity is introduced, and the mapping between colour and temperature is established based on warm and cold colours. Considering the lower resolution of the tactile channel, six limited stimulation levels are generated to represent colours. Based on the semi-infinite body model, the thermal response within the skin for each stimulation form is investigated. The Peltier element of the display is designed to convey different thermal stimuli to the human finger. Two experiments are performed to evaluate the performance of the display: colour identification and discrimination. Experimental results indicate that there is a response bias among the perceived colours for the traditional method of only employing thermal intensity, but there is no response bias for the proposed method; subjects' mean recognition accuracy with the proposed method is significantly higher than that gained using the traditional method. Furthermore, colour information of the captured images can be reliably discriminated by using this devised thermal tactile display.